The Happy Inbox : How to Have a Stress-Free Relationship with Your Email and Overcome Your Communication Clutter - Thomas, Maura Nevel (Empowered Productivity, 2022)
Get ready to learn how to conquer the distractions caused by information and communication overload, and how to get out from under "communication clutter," so you can live a life of choice-one of action, not reaction. Feeling buried by communication clutter is feeling like you are always owing return communication to someone. It's the subtle sense of anxiety caused by your backlog of email, taunting you with the little red indicators on the communication apps on your phone-texts, voicemails, missed calls, social media notifications-plus the mountain of outstanding email piling up in your inbox even as you read this. Want to live free of that feeling?! Get ready to dive in and live free of communication clutter! Positive results include: - Reduced anxiety caused by digital and paper clutter. - An ability to retrieve information you need quickly. - The opportunity to spend less time managing communication clutter and more time working toward your goals!